Volatome finger printing of red wines made from grapes grown under tropical conditions of India using thermal-desorption gas chromatography–mass spectrometry (TD–GC/MS) - Somkuwar, R. G. (J Food Sci Technol, 2019)
The current study evaluated the key characters of aroma composition in diversified red wines (Cinsaut, Grenache, Cabernet Franc, Petit Verdot, Cabernet Sauvignon, Nielluccio, Tempranillo, Syrah, Merlot and Caladoc). Out of hundreds of volatile compounds 64 compounds were considered for study. Different groups consisting of fatty acids, volatile alcohols, aldehydes, esters, volatile phenols and terpenes were analysed using gas chromatography mass spectrometry coupled with thermal desorption (TD–GC–MS). Among all these diversified classes, alcohols were found as the most dominant group followed by esters and acids whereas aldehydes, phenols and terpenes were found to be minor compounds. Among the varieties, Nielluccio wine recorded highest concentration of total volatile compounds (191.53 mg/L) while, it was least in Caladoc wines (15.45 mg/L). The principal component analysis clearly differentiated Grenache wines based on their relationships between scores and their aroma composition followed by Nielluccio and Cinsuat wines. Out of sixty four compounds, only six aromatic compounds viz. butanediol, isoamyl actate, γ-Terpene, butanol, acetic acid and furfural have satisfying aroma descriptors with floral and fruity nuances and contribute to differentiate the Grenache wines from other varieties which have similar scores in PC1 analysis. The cluster analysis also suggested that the wines in the same group (Cinsaut, Tempranillo and Syrah), (Cabernet Franc, Cabernet Sauvignon, Caladoc and Merlot) and (Nielluccio and Petit Verdot) had similar aroma characterization. Grenache wines were well differentiated from the sub group formed by other red varieties. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-019-04147-0) contains supplementary material, which is available to authorized users.